Keamanan Mikrobiologis Air Minum Isi Ulang dan Perubahannya Selama Penyimpanan - Tasya Fitri Yunada; Winiati Pudji Rahayu; Dian Herawati (Jurnal Ilmu Pertanian Indonesia, 2023)
Indonesians use refilled drinking water which can be obtained at depots because of practical and affordable reasons. Low levels of sanitation and hygiene and storage of refilled drinking water for an extended period can lead to the possibility of the growth of indicator and pathogenic microorganisms such as Coliform and Escherichia coli (E. coli). This study aims to evaluate the application of drinking water refilling stations (DWRS) sanitary hygiene, microbiological quality and safety of refilled drinking water and its changes during storage. Samples of refilled drinking water were taken from two DWRSs for each region in five areas of DKI Jakarta including West, East, South, North, and Central Jakarta. The treatments in this study were refilled drinking water storage in gallons of closed and open-closed conditions at room temperature (28 + 2°C) for 0, 7, and 14 days. The results of observations showed that 30% (n=30) of depots complied with hygiene sanitation standards according to Permenkes RI No. 43 of 2014 (>70%). The analysis results showed that refilled drinking water at 0 days of storage, 100% met the TPC (5 Log CFU/mL), 20% met the total Coliform standard (0 Log CFU/mL), and 80% met the E. coli standard (0 Log CFU/mL) according to Permenkes RI No. 492 of 2010. Storage times of 0, 7, and 14 days of refilled drinking water had a significant effect on TPC and total Coliform (P < 0.05), but had no significant effect on E. coli (P > 0.05) in gallons with closed and open-closed conditions. Keywords: Coliform, DWRS, E. coli, refilled drinking water